1978
DOI: 10.3109/00016347809155890
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Death Due to Infection with Group B Streptococci

Abstract: During the 6-year period 1970-1975 5 cases of late intrauterine death caused by group B streptococcal infection were seen in two obstetrical departments in the Stockholm area. During the same period 17 638 infants were born in the two departments, and in 117 cases intrauterine death occurred. Hematogenous spread of the infection from the mother was the most likely cause in the 5 cases. This figure should be compared with a carrier rate of 15-20% in pregnant women in the Stockholm area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…30 The reported rates across Swedish studies from the 1970s and 1980s were highly consistent (0.2-0.3 per 1000 births). 19,21,22,24 Additionally, data from 11 studies suggested that the proportion of GBS among infection-related stillbirth ranged from 0 to 50%.…”
Section: Gbs-related Stillbirthmentioning
confidence: 99%
See 2 more Smart Citations
“…30 The reported rates across Swedish studies from the 1970s and 1980s were highly consistent (0.2-0.3 per 1000 births). 19,21,22,24 Additionally, data from 11 studies suggested that the proportion of GBS among infection-related stillbirth ranged from 0 to 50%.…”
Section: Gbs-related Stillbirthmentioning
confidence: 99%
“…Of the 17 included publications, ten studies were conducted before 1990, five in the 1990s, and only two were conducted since 2000. Five reports were identified from Sweden, 19,21,22,24,35 four from the USA, 23,29,30,34 two from Canada, 25,26 and one each from Zimbabwe, 33 Mozambique, 28 Lithuania, 31 Italy, 32 England, 27 and New Zealand. 20 A variety of different study designs were used, including three case-control studies, eight prospective cohort studies, and five retrospective reviews of autopsy files.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, other human pathogens including parvovirus B19, which can cause intrauterine fetal death, have been linked with erythroblast apoptosis [50]. Interestingly, intrauterine fetal death has also been strongly associated with GBS infections [3, 51, 52]. These observations suggest that GBS-induced erythroblast apoptosis may play a role GBS-associated intrauterine fetal death.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of early-onset infection in human neonates born to colonized mothers with intact or recently ruptured membranes could be similar to that occurring in this animal model. Hematogenous transmission of GBS from mother to infant has been suspected as occurring, particularly in the presence of intact membranes (8). The importance of this mode of transmission of infection, however, is not well understood.…”
Section: Discussionmentioning
confidence: 99%